People detection and tracking in videos - Chu, Bowen (2016)
This is the student’s final year project report, and it mainly talks about the demonstration of detecting and tracking people. There are two parts contained in this paper. The first part is the people detection part. It uses the method of Histogram of oriented gradients to recognize the people within the cameras. Moreover, the second part is the people tracking part. The image subtraction method would be applied for recording the path of moving people. In addition, the project would be developed by C++ programming language, and the VS and OpenCV should be used to solve the problem.